A Review of Herbal Treatment for Functional Gastrointestinal Disorders and Infection - Krupavaram, B; Babu, Ancha Kishore; Santhiya, Manickam Pillay; Tan, Ching Siang; Bama, V.V. Menon; Ganesh, Sritheran Paneerselvam; Long, Chiau Ming *; Al-Worafi, Yaser Mohammed; Chooi, Wen Han (HH Publisher, 2023)
Functional dyspepsia (FD), a common gastrointestinal condition, poses significant burdens on both individuals and society. In this article, we conducted PubMed searches using specific keywords to review clinical trials focusing on conventional and herbal treatments for dyspepsia as well as the adverse effects of non-herbal treatments. Dyspepsia can be managed using proton pump inhibitors, H2 blockers, and antacids. Additionally, we explore Tegaserod, a partial agonist of the 5-HT4 receptor, in the context of prokinetic medications. We summarise the research supporting the effectiveness of non-herbal dyspepsia treatment, considering factors beyond acid reduction, such as the placebo effect and the variability of dyspepsia symptoms, as discussed in the section on proton pump inhibitor (PPI) medication. Unlike most pharmacotherapies targeting a single mechanism, herbal medications often contain multiple active ingredients that can address several signalling pathways simultaneously. Notable herbs like fennel, cumin, aloe vera, ginger, and licorice have documented uses in the literature. Whether derived from a single plant or a combination, herbal treatments hold promises for addressing multiple conditions simultaneously. Therefore, evaluating herbal therapy at all stages of development should adhere to the same scientific rigour applied to chemically specific